Motivation, Frustration Tolerance and Satisfaction Scales in School Context: Three Short Scales - Cuadros Jiménez, Olga (2024)
This study proposed the design of three brief scales coherent with and contributing to the pedagogical perspective of schoolteachers, aiming to enhance self-regulated learning and psychological well-being of students. With the participation of teachers and other professionals who provided feedback throughout the process, scales for school motivation (ME), frustration tolerance (TF), and school satisfaction (SE) were designed and validated among 1260 students from 7th to 12th grade (57.7% female, mean age M=14.9 years, SD=1.9) belonging to three educational institutions in northern Chile. Descriptive, correlational, reliability, and confirmatory factor analysis (CFA) measures obtained indicated adequate psychometric behavior in all scales. As a result of the validation process, the report indicates that the instruments meet psychometric criteria for application in the school context and contribute to identifying strengths and motivational, affective, and satisfaction needs of students, relevant to their processes of self-regulated learning and psychological well-being.